53.4k views
0 votes
If F(x) = 1/9x -2, what is f-1(x)?

f-1(x) = 9x + 18
f-1(x) = 5x+2
f-1(x) = 9x+2
f-1(x) = -2x +

2 Answers

4 votes

Answer:

a)

on edg 2020

Explanation:

edgen

User Balah
by
4.8k points
5 votes

For this case we must find the inverse of the following function:


f (x) = \frac {1} {9} x-2

To do this, we follow the steps below:

We change
f (x)by y:


y = \frac {1} {9} x-2

We exchange the variables:


x = \frac {1} {9} y-2

We clear the variable "y":


x + 2 = \frac {1}{9} y\\9 (x + 2) =y\\y = 9 (x + 2)\\y = 9x + 18

Finally, we change "y" to
f^(-1)(x):


f^(-1)(x) = 9x + 18

ANswer:

The inverse of the given function is:
f^(-1)(x) = 9x + 18

User Dusan Kovacevic
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.